Pengaruh Budaya Organisasi Islam dan Prophetic Leadership Terhadap Kinerja Karyawan - Ardi Juniariah, dkk, Fauziah (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2026)
Employee Performance in the Marketing Division of CV. Fashion Muslim has experienced fluctuations in aspects of discipline, work quality, and productivity over the past four months. This study aims to describe and analyze the influence of Islamic Organizational Culture and Prophetic Leadership on Employee Performance in the Marketing Division of CV. Fashion Muslim, both partially and simultaneously. This study employed a quantitative approach with a saturated sampling technique where the entire population of 57 employees were used as respondents. Data were collected through questionnaires distributed digitally via Google Form and in physical form, then analyzed using multiple linear regression analysis with SPSS 22. The results showed that the implementation of Islamic values in organizational culture was in the fairly high category (85.789%) and the Prophetic Leadership style was in the high category (80.61%), while Employee Performance was categorized as fairly high (84.13%). Partially, Islamic Organizational Culture had a positive and significant effect on Employee Performance with a t-count value of 7.123 > t-table 2.005, and Prophetic Leadership also had a positive and significant effect with a t-count value of 4.500 > t-table 2.005. Simultaneously, both variables had a very significant effect with an F-count value of 66.858 > F-table 3.17, explaining 71.2% of performance variance, while the remaining 28.8% was influenced by other factors such as compensation, work motivation, work environment, and employee competence. This demonstrates that the combination of Islamic Organizational Culture and Prophetic Leadership creates an effective synergy in supporting the improvement of work quality, productivity, and optimal achievement of organizational goals. Keywords: Employee Performance, Islamic Organizational Culture, Prophetic Leadership